2002
DOI: 10.1152/japplphysiol.00072.2001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in regional cerebral metabolism during systemic hyperthermia in humans

Abstract: Whole body hyperthermia may produce vasodialation, nausea, and altered cognitive function. Animal research has identified brain regions that have important roles in thermoregulation. However, differences in both the cognitive and sweating abilities of humans and animals implicate the need for human research. Positron emission tomography (PET) was used to identify brain regions with altered activity during systemic hyperthermia. Human subjects were studied under cool (control) conditions and during steady-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…Systemic hyperthermia significantly increases cerebral metabolic rate in adult humans (23%) (13), and in newborn pigs (65%) (12). In parallel with the increase in cerebral metabolic rate, there is a sharp (by 97%) rise in CBF in response to systemic hyperthermia in pigs (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic hyperthermia significantly increases cerebral metabolic rate in adult humans (23%) (13), and in newborn pigs (65%) (12). In parallel with the increase in cerebral metabolic rate, there is a sharp (by 97%) rise in CBF in response to systemic hyperthermia in pigs (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether the collateral circulation is sufficient to meet increased cerebral metabolic demands. It is well established that systemic hyperthermia (fever) significantly increases cerebral metabolic demand and is associated with a steep increase in CBF (12,13). Given that permanent loss of the CAϩJV can potentially limit the rise in CBF in response to metabolic demand, we hypothesized that systemic hyperthermia/fever may induce cerebral ischemia in a hemisphere that has undergone CAϩJV ligation.…”
mentioning
confidence: 99%
“…These authors reported glucose utilisation to be minimally altered or slightly higher in the thalamus and neocortex. Changes in regional cerebral metabolism have also been studied with FDG-PET in humans during steadystate hyperthermia [52]. This study reported a significant increase in FDG in the hypothalamus, thalamus, corpus callosum, cingulated gyrus and cerebellum, as well a significant decrease in the caudate, putamen, insula and posterior cingulum.…”
Section: Short-term Effects On Brain Glucose Metabolismmentioning
confidence: 94%
“…It is generally accepted that heat stress, both passive and exertional, increases global CMRO 2 (325,326,365). Animal studies suggest that local cerebral and whole-body hyperthermia of up to 43 • C core temperature increase global cerebral glucose utilization (289, 296) and associated CMRO 2 by ∼5% to 10% per degree Celsius rise in core temperature (62,72,321,322).…”
Section: Metabolic Regulation Of Cerebral Blood Flow Cerebral Metabolismmentioning
confidence: 99%